Estimulación cognitiva y su incidencia en el aprendizaje significativo a estudiantes de la unidad educativa “león de Febres Cordero”, Parroquia San Juan, cantón Pueloviejo, Provincia los Ríos - Villacís Gonzalez, Zaida Yasmín (2016)
At birth, all alike we have an enormous potential, which depends on our condition of being human. In the first six years of life, our brain has a learning ability and intelligence development in all its aspects without intrinsic limits. The only obstacles tend to be adults, who for a limited time, ignorance or mistaken beliefs do not provide adequate or sufficient quantity stimulation. To that early stimulation is adequate must be integral (which includes the intellectual, emotional and social aspects simultaneously), taking into account the limitations of the senses and take advantage of the peculiarities of learning during this period. For an infant, the best conditions of stimulation with the features mentioned are only achieved at home with their own parents or guardians being teachers. Positively stimulate a child is educated with good roots. Early education is to enhance the sensitive periods, which are the right moments in which the child assimilates determined learning easier. Hence the importance of cognitive stimulation, which is based on knowing where to focus educational efforts according to the ages of the children and encourage them properly.